Poetics of the route: to lose oneself in Bas Jan Ader (Palíndromo, 2019)
This article intends to discuss the concept of losing oneself in Dutch artist Bas Jan Ader, focusing on the trilogy In Search of the Miraculous. To lose oneself would be understood as an experience of launching into the present and allowing external forces to define your route, and therefore, we approach Ader with the romantic experience.
Keywords: route; loss; Bas Jan Ader; romanticism